2021
DOI: 10.18203/2349-2902.isj20214003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between direct safety trocar insertion versus veress needle technique for creating pneumoperitoneum in laparoscopic surgeries

Abstract: Background: There are two methods of trocar insertion in laparoscopic surgeries one is direct insertion and second is Veress needle insertion. In this study we compared these two methods.Methods: In this study we divided 50 patients equally into two group group A for in group A patients, direct trocar insertion technique was used for creation of pneumoperitoneum whereas amongst patients of group B, pneumoperitoneum was created using Veress needle insertion technique.Results: The incidence of visceral injuries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In an attempt to de ne user requirements better, literature about the insertion procedure was consulted. Studies by Vaishnani et [14,15]. However, Azevedo et al, reported that insertion at the midline should be avoided as the risks related to overshooting in organs is too high [16].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to de ne user requirements better, literature about the insertion procedure was consulted. Studies by Vaishnani et [14,15]. However, Azevedo et al, reported that insertion at the midline should be avoided as the risks related to overshooting in organs is too high [16].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to define user requirements better, literature about the insertion procedure was reviewed. Studies by Vaishnani et al and Datey et al indicate that there are no significantly different outcomes when open and closed techniques are compared in a more generic way 14 , 15 . However, Azevedo et al, reported that insertion at the midline should be avoided as the risks related to overshooting in organs is too high 16 .…”
mentioning
confidence: 99%